Prediction of Consciousness Recovery in Coma after Traumatic Brain Injury by Disorder of Consciousness Scale (DOCS) - Kavusipur, Somaye (Bull Emerg Trauma, 2013)
OBJECTIVE: To determine the prediction value of disorder of consciousness scale (DOCS) for consciousness recovery after traumatic brain injury (TBI) leading to coma. METHODS: This is a descriptive-cross-sectional study of the correlation between the level of patients’ consciousness in the first and second weeks and the first 2 months after traumatic brain injury, using DOCS scale. RESULTS: The findings of the present study showed that the sensitivity and specificity of DOCS in determining individual’s consciousness after first week and two months after injury are 66% and 41% respectively, and regarding DOCSU2 the corresponding values were 94% and 50% (p=0.001). CONCLUSION: Passage of time is one of the most significant factors in predicting the resumption of consciousness in patients with brain injury, and more accurate results are expected following the acute phase. However, the application of disorder of consciousness scale could be of a great help to patients’ families and rehabilitation staff in regard to providing a better services to meet the patients” future needs.